2021
DOI: 10.1002/ccr3.4328
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis associated with HBV‐HCV coinfection in adult: Case report

Abstract: The case reported is the first case in Morocco to our knowledge. The reason for sharing this case is to facilitate knowledge transfer between physicians, caring for adult patients with HLH, with the aim to improve the outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Moreover, HLH can result from infection with hepatitis viruses, with the majority of cases involving HAV and, less commonly, HBV or HCV infection [92][93][94]. Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
“…Moreover, HLH can result from infection with hepatitis viruses, with the majority of cases involving HAV and, less commonly, HBV or HCV infection [92][93][94]. Two systematic reviews of HAV-associated HLH cases have identified hepatomegaly and splenomegaly as distinguishing features of HAV-HLH, as these signs are rarely observed in patients with HAV infection who do not develop HLH [63,95].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
“…Human herpes virus (HHV), Epstein-Barr virus (EBV), and cytomegalovirus (CMV) are among the most common viruses associated with HLH. However, cases of influenza (H1N1 and H5N1), parvovirus B19, and hepatitis A and C-associated HLH have been reported [ 18 , 19 ]. Various mechanisms have been described as possible drivers for HLH in viral infections [ 20 ].…”
Section: Reviewmentioning
confidence: 99%